Bibliometric Analysis of Research Trends in Christian Religious Education Teacher Competencies for the 2014-2023 Period - Hisardo Sitorus (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This research aims to analyze research trends in Christian religious education teacher competency for the 2014-2023 period and provide relevant insights for Christian religious education practitioners. The research method used is bibliometric analysis, drawing data from 212 articles from the Dimension database that had successfully undergone the data collection phase. The analysis results show a significant increase in publications relevant to the competency of Christian religious education teachers since 2016, reaching the highest peak in 2022. The research focus on this topic is very diverse, covering practical aspects such as teacher performance, understanding of concepts, and the role of parents and culture in Christian religious education. However, the lack of collaboration between authors, countries, or institutions in this research is a limitation that needs to be considered.